Risk competence in dealing with alcohol and other drugs in adolescence - Nagy, Ede; Verres, Rolf; Grevenstein, Dennis (Substance use & misuse, 2017)
Background: Adolescence is a critical phase for the development substance use patterns. We propose that individual competence in dealing with psychoactive substances is crucial for the development of healthy substance use behavior and prevention of substance misuse or addiction. Objectives: We present a new concept of health related skills in dealing with alcohol and other drugs in adolescence, its operationalization and validation. Our conception of risk competence (RICO) consists of the four major factors being Reflective, Informed, Self-Controlled and Life-Oriented, and their sub-facets. Methods: Based on a sample of N = 753 adolescents we used classical test theory as well as item response theory to create a new measure of RICO. Validity was investigated in a new sample of N = 229 with regard to substance use, risk perception, and measures of personality (Big Five, sense of coherence, general self-efficacy). Results: RICO contains 7 scales with 28 items that measure independent aspects of risk competence. Cross-sectional criterion validity for most of the scales could be shown. Conclusions/Importance: The new RICO scales are a valid measure of different aspects of risk competence in dealing with psychoactive substances. The questionnaire can be used in general research settings, but may also be applied to assess the effects of interventions.